Quebec Health-Related Quality-of-Life Population Norms Using the EQ-5D-5L: Decomposition by Sociodemographic Data and Health Problems - Poder, Thomas G.; Carrier, Nathalie; Kouakou, Christian R.C. (Value in health, 2020)
Population norms for the EQ-5D-5L were published in Canada but only for Alberta province. The purpose of this study was to derive Quebec population norms from the EQ-5D-5L. The data came from a larger study conducted between September 2016 and March 2018 using elicitation techniques for a quality-adjusted life-year project. The online survey was distributed randomly in the province of Quebec. To best describe the entire population, data were stratified by various sociodemographic characteristics such as age, gender, urban and rural populations, whether disadvantaged or not, immigrant or nonimmigrant, and health problems. A total of 2704 (53.8%) respondents completed the EQ-5D-5L. Mean (95% confidence interval) and median (interquartile range) utility scores were 0.824 (0.818-0.829) and 0.867 (0.802-0.911), respectively. The EQ-VAS scores were estimated at 75.9 (75.2-76.6) and 80 (69-90). Subjects with lower scores were those who had a low or high body mass index; were smokers; were single, divorced, or widowed; had no children; were unemployed or sick; had lower education or lower annual income; and had a family or personal history of serious illness. Immigrants had higher scores. There was no difference in gender and urban or rural population. The score logically decreased with worsening health status, from a mean score of 0.896 (0.884-0.908) to 0.443 (0.384-0.501; P < .0001. Similar results were observed for subjects’ satisfaction with their health or life. Subjects with lower scores were less willing to take risks. Subjects who declared they were affected by health problems presented significant lower utility scores, ranging from 0.554 (nervous problem) to 0.750 (cancer), compared with those without health problems (0.871; confidence interval: 0.867-0.876). This is the first study to present utility score norms for EQ-5D-5L for the Quebec population. These results will be useful for comparison with quality-adjusted life-year studies to better interpret their results. Moreover, utility norms were provided for 21 health problems, which was rarely done.